1997
DOI: 10.1002/ls.3010100104
|View full text |Cite
|
Sign up to set email alerts
|

A study of the rheological behaviour of multigrade oils

Abstract: The rheological behaviour of four blends of multigrade oils containing different commercial viscosity index improvers has been studied for increasing shear rate and temperature. Polyalkylmethacrylate has been found to demonstrate different behaviour to styrene‐isoprene, styrene‐butadiene and ethylene‐propylene copolymers. Oil blends for all these hydrocarbon copolymers have shown non‐Newtonian behaviour with increasing shear rate (0 to 35,000 s−1) at low and moderate temperatures (−15 to 40°C), i.e. their visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…The values of dynamic viscosity versus the shear rate at 40 and 100°C are given in Figure 6A,B. From the results, it is clear that the non‐Newtonian behavior was observed for pure lube oil at a lower shear rate while at a higher shear rate it follows the Newtonian behavior 38 . For lube oil blended with polymeric additives at 5000 ppm of concentration, it is found that viscosity gradually decreases at the low shear rate (5–35 s −1 ) while remains constant at the higher shear rate 39 .…”
Section: Resultsmentioning
confidence: 92%
“…The values of dynamic viscosity versus the shear rate at 40 and 100°C are given in Figure 6A,B. From the results, it is clear that the non‐Newtonian behavior was observed for pure lube oil at a lower shear rate while at a higher shear rate it follows the Newtonian behavior 38 . For lube oil blended with polymeric additives at 5000 ppm of concentration, it is found that viscosity gradually decreases at the low shear rate (5–35 s −1 ) while remains constant at the higher shear rate 39 .…”
Section: Resultsmentioning
confidence: 92%
“…Figures (1) through (3) shows a rheological study of Polymethacrylates that has been carried out by M.H.M. Hassanean [4]. The blends have been studied at different temperatures and shear rates and the results showed the same behavior.…”
Section: Introductionmentioning
confidence: 89%
“…This generates more friction which in turn generates more heat. Energy or power losses and poor cold starting pumpability can also all resulted from lubricant over-thickening [4]. However, too low viscosity is not desirable too, as it causes excessive wear due to the loss of the load bearing characteristics of the oil.…”
Section: /16mentioning
confidence: 99%
“…The viscosity of the lube oil without any additives is approximately constant with increasing the shear rate. This indicates that pure lube oil behaves like a Newtonian fluid at any shear rate [33]. For lube oil with additives, it is found that at low shear rate (5-30 s -1 ), the viscosity gradually decreases and the lubricant behaves like a non-Newtonian fluid [34].…”
Section: Analysis Of Rheological Studymentioning
confidence: 96%